Adding of apatinib and camrelizumab to overcome de novo trastuzumab resistance of HER2-positive gastric cancer: A case report and literature review - Lv, Huifang; He, Yunduan; Nie, Caiyun; Du, Feng; Chen, Xiaobing (Frontiers in Pharmacology, 2023)
Background: It is confirmed that trastuzumab plus fluorouracil-based chemotherapy improves the survival to more than one year in HER2-positive advanced gastric cancer. However, there is still a small proportion of patients who do not benefit from trastuzumab treatment. Case summary: Here, we described a case report of de novo trastuzumab resistance in HER2-positive gastric cancer. Concomitant CCNE1 and HER2 amplification is associated with de novo trastuzumab resistance. Genomic analysis demonstrated CCNE1 amplification and TP53 mutation in a HER2-positive gastric cancer patient. This patient achieved significant survival benefit and good safety when she received triple regimens consisting of trastuzumab, apatinib and camrelizumab. Conclusion: camrelizumab plus apatinib plus trastuzumab has the potential efficacy in HER2-positive gastric cancer patients who previously treated with trastuzumab plus chemotherapy, this may lead to a new solution to trastuzumab resistance.